Full Recovery of a Cross-bred Cat from Bacterial Mycoplasmosis, Protozoan Babesiosis, and Other Co-current Diseases: A Case Report - Budiono, Novericko Ginger; Rachmawati, Nela; Delimasari, Zahrizada Zamrudina; Muryani, Astri; Natawiria, Maria Stella Linda; Rabbani, Syafina Syafaatur; Tuliman, Nurul Annisa; Islami, Nurfara; Fitri, Arni Diana (Jurnal Veteriner, 2025)
This report aimed to describe a diagnosis and treatment of feline mycoplasmosis that co-occurs with babesiosis and other diseases in a one-year-old male uncastrated mix-domestic cat. The patient was presented to the first clinic with pale, lethargy, and inappetence. After one week, the patient was presented to a second clinic due to the owner’s inability to provide home treatment. Clinical examinations revealed pale to jaundiced mucous membranes, caries dentis, gingivitis, fur mite infestation, and flea infestation. Haematology revealed anaemia and thrombocytopenia. Blood chemistry showed increased alanine aminotransferase, total protein, and blood urea nitrogen. Ear native observation revealed ear mite infestation. Blood smear cytology revealed that the patient has intraerythrocytic Mycoplasma and Babesia infections, so diagnoses of mycoplasmosis, babesiosis, fur mite infestation, flea infestation, ear mite infestation were made. The patient was hospitalised in both clinics for a total of 30 days. The treatments were doxycycline as anti- Mycoplasma /anti- Babesia  treatment and supportive therapy such as infusion and blood supplement. Ectoparasiticides were also given to the patient to kill external parasites. Dental scaling was applied to treat caries dentis and gingivitis. In conclusion, this study reportedthat the cat was fully recovered after the treatments and the patient was discharged from hospitalisation.